Physical dysfunction practice skills for the occupational therapy assistant - Early, Mary Beth (St. Louis, Mo. Mosby Elsevier, 2006)
Designed as both a practical clinical reference and a comprehensive classroom text, the second edition of Physical dysfunction practice skills for the occupational therapy assistant offers a focused, easy-to-use approach to physical dysfunction. This new edition provides updated and expanded coverage of issues related to work, habits of health and wellness, leisure and social participation, and activities and occupations of daily living
Part I History and foundations 1 -- Part II Framework and Process -- Part III Assessment of client factors -- Part IV Intervention principles -- Part V Performance in areas of occupation -- Part VI Interventions for performance skills and client factors -- Part VII Clinical Applications
Includes bibliographical references and index
CHK-1012g Donated by CD Books International, Inc
Keywords: Occupational therapy assistants; People with disabilities -- Rehabilitation; Occupational Therapy; Allied Health Personnel